2012
DOI: 10.3109/09638288.2012.665125
|View full text |Cite
|
Sign up to set email alerts
|

Inter-physician agreement on the readiness of sick-listed employees to return to work

Abstract: The inter-OP agreement on intuitively rated RRTW showed a wide variability, which accentuates the need for instruments to establish an employee's RRTW and for training in giving well founded return to work recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
2
5
0
1
Order By: Relevance
“…Our findings expand previous understanding of the relevant knowledge, skills and attitudes needed from occupational health practitioners, as well as the multi-level environmental factors that influence the application of work modifications [ 11 15 , 35 38 ]. By utilizing the TDF we were able to conduct a comprehensive theory-informed assessment of all potential factors that influence OPs’ key behaviors.…”
Section: Discussionsupporting
confidence: 79%
“…Our findings expand previous understanding of the relevant knowledge, skills and attitudes needed from occupational health practitioners, as well as the multi-level environmental factors that influence the application of work modifications [ 11 15 , 35 38 ]. By utilizing the TDF we were able to conduct a comprehensive theory-informed assessment of all potential factors that influence OPs’ key behaviors.…”
Section: Discussionsupporting
confidence: 79%
“…Of 4562 potentially relevant citations identified, 101 reports proved potentially eligible after we had screened titles and abstracts. On full text screening, 23 studies, 9 11 22 23 24 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 including four non-English studies, 9 39 40 41 proved eligible for analysis (fig 1 ). All studies were published from 1992 onwards and enrolled disability claimants from 12 countries in Europe, North America, Australia, the Middle East, and northeast Asia.…”
Section: Resultsmentioning
confidence: 99%
“…In the insurance setting, 13 studies including 463 patients and 367 raters explored agreement between medical experts (two or more experts assessing the same patient) (table 1 ; appendix 4). 9 11 22 23 24 32 34 37 39 43 44 45 46 Three studies including 3729 patients (with 3562 patients from a single centre 33 ) and eight raters (information was lacking from one study 33 ) explored agreement between medical experts and claimant’s treating physicians 33 or independent rehabilitation or occupational health teams with a mandate to care. 38 42 The median number of patients per study was 13.5 (range 1-3562), and the median number of raters per study was 12 (2-103, excluding one study that did not report the number of raters 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a Dutch study, it was found that OPs who had training regarding existing evidence for return-to-work prognosis, and who performed scientific database searches regularly, did succeed better in advising interventions, but not in providing correct prognoses for their patients, compared with a control group [25]. An inter-individual variability has been shown to exist among OPs for decisions concerning assessment of fitness for work [26,27]. In several studies, proposals of methods for increasing quality in predicting sick leave duration among OPs are put forward [13,14].…”
Section: Discussionmentioning
confidence: 99%